Posisi Negara Dalam Menangani Kepemilikan Publik: Distribusi Tanah Milik Negara Dalam Membangun Ekonomi Masyarakat Miskin - Yuke Rahmawati (Esensi: Jurnal Bisnis dan Manajemen, 2015)
Land is a fundamental part of human life. In fact, people's access to land is very small, even lost due to government regulation in this sector does not support. The state policy through land reform regulations Act 56 of 1960 that people should not have more than five hectares of land (java), seems not yet realized properly. With literacy studies, the authors attempt to compile the various views, both in theory and concepts in order to find the position of the state in improving the local economy through a policy of land distribution.DOI: 10.15408/ess.v5i2.2342